A Biliary Endoprosthesis Functioning After Six Years. Issue 2 (1994) - Plumer, Alan; Iswara, K.; Siegel, Jerome H.
Abstract : The functional lifetime for biliary endoprostheses has typically been 7 months. When combined with sphincterotomy for common bile duct stones, it affords an alternative to surgery in high risk patients. Biliary endoprostheses often require replacement in these patients, though recent reports suggest they are functioning longer. We present an 85-year-old asymptomatic woman with a 6-year-old biliary endoprosthesis, believed to be the longest functioning stent reported in the literature.